Solution
g(x) = 2 - 11x
Plugging in x = -1 in g(x), we get
g(-1) = 2 - 11(-1)
Now we have to simplify it.
g(-1) = 2*1 + 11
g(-1) = 2 + 11
g(-1) = 13
So the answer is D) 13.
Thank you. :)
What exactly are you asking?
Answer:
19.34cm
Step-by-step explanation:
Rigth Angled triangle
use SOHCAHTOA
Cos°=adj/hyp
Cos 71=6.3/BC
BC=6.3/COS 71
COS 71°= 0.3256
BC=6.3/0.3256
BC= 19.34cm
Answer:
x=5
Step-by-step explanation:
2x−7=−3x+18
Step 1: Add 3x to both sides.
2x−7+3x=−3x+18+3x
5x−7=18
Step 2: Add 7 to both sides.
5x−7+7=18+7
5x=25
Step 3: Divide both sides by 5.
5x
5
=
25
5
x=5
Answer:
n= 4
Step-by-step explanation:
3 multiplied by n is 3n.
3 multiplied by -5 is -15.
so 3n-15= 7-2(n+1)
7-2(n+1) is -2 multiplied by n is -2n and -2 multiplied by 1 is -2.
3n-15=7-2n-2
then move the variables to one side and numbers to the one side.
3n+2n=15+7-2
*If you are moving across the equation the symbols change. Like negative to positive. Division to multiplication.
so 5n=22-2
5n=20
5 multiplied by 4 is 20 so n is going to be 4.
N=4